2015
DOI: 10.1016/j.jvs.2015.06.132
|View full text |Cite
|
Sign up to set email alerts
|

The effect of location and configuration on forearm and upper arm hemodialysis arteriovenous grafts

Abstract: Patency was comparable between fAVG and uAVG despite the larger caliber veins often encountered in the upper arm in carefully selected patients. Our findings support the traditional view that, in order to preserve a maximal number of access sites, the forearm location should be considered first before resorting to an upper arm graft.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
15
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(16 citation statements)
references
References 34 publications
1
15
0
Order By: Relevance
“…2 The current investigation informs the scarcely described topic of international AVG creation and successful use. Successful AVG use observed for the United States in DOPPS is consistent with that reported in the Dialysis Access Consortium Trial, 27 although end points were defined somewhat differently. Early failures were considerably more common for newly created AVGs versus AVFs in the current work.…”
Section: Discussionsupporting
confidence: 71%
“…2 The current investigation informs the scarcely described topic of international AVG creation and successful use. Successful AVG use observed for the United States in DOPPS is consistent with that reported in the Dialysis Access Consortium Trial, 27 although end points were defined somewhat differently. Early failures were considerably more common for newly created AVGs versus AVFs in the current work.…”
Section: Discussionsupporting
confidence: 71%
“…Patency was comparable between forearm AVG and upper-arm AVG, although the larger caliber veins were often encountered in the upper-arm. 9) Our study showed no statistically significant difference in the primary patency between outflow vein sizes smaller than and larger than 3 mm (526 days [IQR: 347, 835] versus 409 days [IQR: 149, 739], P=0.380), and the correlation between outflow vein sizes was negative. This correlation means that when the outflow vein size is increased, the primary patency is reduced, but with no statistical significance as well (P=0.237).…”
Section: Discussionmentioning
confidence: 44%
“…In the present study, the autologous AVF failure rate at 6 weeks was 23 per cent with placebo and 28 per cent after GTN, and is broadly consistent with other studies. This is slightly higher than the rate in the US Dialysis Access Consortium Study which, although widely quoted as having a failure rate over 50 per cent, actually had a 15·8 per cent thrombosis rate within 6 weeks of fistula creation.…”
Section: Discussionmentioning
confidence: 59%